Incomplete basic vaccination and associated factors among children aged 12–23 months in resource-limited countries: a spatial and multilevel regression analysis of recent DHS data from 48 countries - Mihret Getnet; Mihret Getnet; Melak Jejaw; Tadele Biresaw Belachew; Banchlay Addis; Endalkachew Dellie; Tesfahun Zemene Tafere; Nigusu Worku; Demiss Mulatu Geberu; Lake Yazachew; Getachew Teshale; Misganaw Guadie Tiruneh; et al. (Frontiers in Public Health)
BackgroundChildhood basic vaccinations are a cost-effective and essential preventive health strategy globally in resource-limited nations. The United Nations Sustainable Development Goals aim to reach these ambitious targets, making it crucial to identify underserved populations and address the barriers they face in accessing life-saving immunizations. To date, no spatial analyses have been performed to identify areas of hotspots of incomplete basic vaccination among children in resource-limited countries globally. Therefore, determining the geographic distribution of incomplete basic vaccinations and associated factors is important for prioritizing intervention programs in resource-limited countries.ObjectiveThis study aims to assess incomplete basic vaccinations and associated factors among children aged 12–23 months in resource-limited countries based on the recent Demographic and Health Survey (DHS) data of 48 countries.MethodsData for the study were drawn from the DHS, a nationally representative cross-sectional survey conducted by considering the era of Millennium Development Goals and Sustainable Development Goals. A total of 48 resource-limited countries and a total weighted sample of 202,029 children (12–23 months) were included in our study. The data extraction, recoding, and analysis were conducted using STATA V.17. For the spatial analysis (spatial distribution, autocorrelation, and hotspot), ArcGIS version 10.7 software was used, and for the SaTScan analysis, SaTScan version 10.1 software was used. Descriptive statistics were presented using frequency tables and percentages. We employed multilevel logistic regression to investigate the associated factors of incomplete basic vaccination. In the multivariable analysis, variables with a p-value of ≤0.05 are considered significant factors associated with incomplete basic vaccination among children aged 12–23 months.ResultsThe overall incompleteness of basic vaccination among children in resource-limited countries was 51% (95%CI: 50–51%). The spatial analysis revealed that the incomplete basic vaccination among children significantly varied across resource-limited countries (Global Moran’s I = 0.208468, p < 0.001). The most likely clusters were located in Nigeria, Chad, Cameroon, and Niger, which were centered at (2.028929N, 15.135990 E)/1425.16 km radius, with a Log-Likelihood Ratio (LLR) of 3519.48 and a Relative Risk (RR) of 1.38 at p-value <0.001. Based on the final model of multilevel analysis, the following variables were statistically significant in relation to incomplete basic vaccination: age, marital status, maternal education, husband’s education, maternal occupation, media exposure, wealth index, antenatal care (ANC) visits, birth order, place of delivery, mode of delivery, health insurance coverage, perception of distance from a health facility, place of residence, community media exposure, community education, and country-level income status.Conclusion and recommendationsThe spatial distribution of incomplete basic vaccination was significantly varied across the resource-limited countries. Both individual- and community-level factors were significantly associated with incomplete basic vaccination. Therefore, the World Health Organization and other stakeholders involved in child healthcare should work together to expand childhood vaccination and prioritize the hotspot areas of developing countries.